2016
DOI: 10.1002/chem.201600313
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a Metal–Organic Framework into 3 D Hierarchical Porous Monoliths Using a Pickering High Internal Phase Emulsion Template

Abstract: 3D Hierarchical porous metal-organic framework (MOF) monoliths are prepared by using Pickering high internal phase emulsion (HIPE) template. Pickering HIPEs were stabilized solely by UiO-66 MOF particles with internal phase up to 90 % of the volume. The effects of internal phase type and volume, as well as MOF particle concentration on the stability of resulting Pickering HIPEs were investigated. Furthermore, by adding small amount of polyvinyl alcohol (PVA) as binder or polymerization in the continuous aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 70 publications
0
74
0
Order By: Relevance
“…The hybrid component of MOF exhibits amphiphilic properties; it can absorb at the interface of two different phases. HKUST‐1 was tested for the emulsification of cyclohexane‐in‐water emulsion (80:20, v/v) to demonstrate the emulsifying effect. The results confirmed that this HIPE could be stabilized for several days (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid component of MOF exhibits amphiphilic properties; it can absorb at the interface of two different phases. HKUST‐1 was tested for the emulsification of cyclohexane‐in‐water emulsion (80:20, v/v) to demonstrate the emulsifying effect. The results confirmed that this HIPE could be stabilized for several days (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…These materials have drawn great attention in many conventional fields in recent years, including storage, adsorption, catalysis, separation, and some novel applications such as biomedicine, guiding agent, sensor material, membrane material, and porous material because of their high surface area, adjustable pore structure, variable chemical functionality, relatively high thermal stability, and ordered porosity. Considering the chemical formation of coordination polymers, MOFs show certain surface activity that allows adsorption at the interface of two immiscible fluids as a Pickering emulsifier …”
Section: Introductionmentioning
confidence: 99%
“…UiO-66 (University of Oslo-66) particles were synthesized according to the literature. [36] Typically,z irconium chloride (915 mg) and terephthalic acid (645 mg) were first dissolved in 225 mL dimethylformamide (DMF) and 6.7 mL of acetic acid was later added into the solution. The mixed solution was then placed at 120 8Cf or 24 h. The white precipitates were then collected by centrifugation, washed with methanol 3times, and finally dried at 60 8Cu nder vacuum for 24 h.…”
Section: Mof Synthesismentioning
confidence: 99%
“…Pickering HIPEs stabilized by UiO-66 were prepared in a2 0mL glass vial by applying ah igh shear force according to the literature. [36] Ta king Sample Ba sa ne xample:P VA was first dissolved in deionized water to prepare 100 mg g À1 aqueous solution. 100 mg of UiO-66 was dispersed in 1.9 mL of water under sonication and 110mgo ft he prepared PVAs olution was added to form an aqueous suspension.…”
Section: Preparation Of Pickering Hipesmentioning
confidence: 99%
“…Relatively larger networked channels will facilitate transportation of HCHO to the interior of an adsorbent . In practice, the success of an adsorbent is not only dependent upon its adsorption capacity but also adsorption–desorption kinetics, and thereby regeneration of saturated adsorbents is another critical factor that must be considered in the development of satisfactory adsorbents …”
Section: Introductionmentioning
confidence: 99%